Althesin: a new intravenous steroid anaesthetic. Issue 13 (22nd June 1973) - Unknown
Abstract : The anaesthetic effects of pregnanedione and other related steroids were first described in 1941. 1 Hydroxydione was the first drug in this group to be used clinically, but it had serious disadvantages. 2 Althesin (Glaxo) is a mixture of two water-insoluble pregnanedione derivatives, alphaxalone and alphadolone, dissolved in Cremophor EL (polyoxyethylated castor oil), for intravenous injection. Alphaxalone is the major constituent; alpha-dolone is less potent and is put in to make alphaxalone more soluble in Cremophor. The solution is viscous, but slightly less so than that of propanidid (Epontol - Bayer), which also contains Cremophor.